Roasted ground pepper seed press-cake sauce: quality, characteristics and palatability - Guo, Bing-Xin; Wang, Rui; Yan, Jin; Jia, Xu-Ping; Qu, Ling-Yu; Yin, Wen-Ting; Liu, Hua-Min; Wang, Xue-De (Italian Journal of Food Science, 2025)
Pepper seed press-cake, the by-product of the pepper seed oil pressing process, can be reused to prepare high-quality sauces with significant potential for application and commercial value. In this study, pepper seed press-cakes obtained by roasting at four temperatures (0, 140, 170, and 200°C) were processed with sunflower oil into sauces. The physical properties, rheological characteristics, texture, microstructure, and sensory characteristics of these four sauces were analyzed. The results indicated that sauces made from pepper seed press-cake roasted at 140 and 170°C exhibited better quality. Roasting decreased the oil separation rate (from 10.90 g/100 g to 8.09 g/100 g) and enhanced the storage stability of the sauces. Rheological and textural analyses revealed that roasting reduced both the viscosity and the textural properties of the sauces. The sensory evaluation indicated that sauces prepared from pepper seed press-cake roasted at 170°C exhibited the most intense roasted and nutty aromas, followed by those roasted at 140°C. In a comprehensive assessment, sauces prepared from press-cake roasted at 140–170°C were deemed more suitable for consumer consumption. This study provides strong technical support for the conversion of pepper seed press-cake into a high-value-added commodity.